Species diversity of bats (Chiroptera) in the Ukrainian Azov Region and features of their residence by seasons. - Volokh, Anatolii; Gorlov, Petro; Siokhin, Valeriy; Polishchuk, Igor; Волох, Анатолій Михайлович; Горлов Петро; Сіохін Валерій; Поліщук Ігор (My University, 2021)
ENG : The article presents the results of regional surveys of bats in 2010–2020 in places planned for the construction of wind farms. With the use of modern ultrasonic detectors, computer programs and an electronic library of voices, 15 species were found in the Ukrainian Azov Region. Their highest diversity (11–13 species) was revealed in places of intensive migration. First of all, these are the sites Armyansk, Chaplynka, and Askania-Nova, which are located between the Dnieper valley and the Crimean Peninsula. Probably, in this area, bats migrating from the northern and north-eastern regions cross the land and join those moving along the Azov coast. The movement of a significant number of animals is noticeable in the west of the Molochna River. A relatively large variety of bats occurs near the sites Botiyevo, Orlivka, and Primorsk, located directly on the northern shore of the Sea of Azov, along which the migratory movements of bats are particularly strong. During win ter, with limited research in this period, 8 species were found, whereas 13 species during spring and autumn migrations and 11 species in summer. The almost complete transformation of the steppe into agrocoenoses bordered by forest belts and irrigation canals undoubtedly affected bats in addition to global warming. In recent years, in all places of the Ukrainian Azov Region, there has been a decline in the number of the common pipistrelle (Pipistrellus pipistrellus) and serotine bats (Eptesicus serotinus), and an increase in the abundance of the noctule bat (Nyctalus noctula), Kuhl's pipistrelle (Pipistrellus kuhlii), Nathusius' pipistrelle (Pipistrellus nathusii), and parti-coloured bat (Vespertilio murinus). In all seasons, the least common species were the brown long-eared bat (Plecotus auritus), Daubenton's bat (Myotis daubentonii), greater noctule (Nyctalus lasiopterus), lesser noctule (Nycta lus leisleri), Savi's pipistrelle (Hypsugo savii), and western barbastelle (Barbastella barbastellus). ///////////////////////// Ukr : У 2010–2020 рр. у регіоні Північного Приазов’я на проміжку від Маріуполя до оз. Сиваш включно у місцях, що заплановані для будівництва вітрових електростанцій за використання 6 сертифікованих ультразвукових детекторів (Pettersson D240х, Pettersson D500x, LunaBat DFR-1 PRO) зафіксовано перебування 15 видів кажанів. На дослідженій території під час зимівлі, за обмежених досліджень у цей період, виявлено 8 видів, упродовж весняної та осінньої міграцій — по 13 видів, а влітку — 11 видів кажанів. В усі сезони найменш поширеними були вухань бурий (P. auritus), нічниця водяна (M. daubentonii), вечірниці велетенська (N. lasiopterus) та мала (N. leisleri), гіпсуг гірський (H. savii) та широковух європейський (B. barbastellus). У географічному вимірі найбільша видова різноманітність кажанів (загалом зареєстрова-но 10–12 видів) виявлена в регіоні на двох ділянках — у найвужчому проміжку між Дніпром та Азовським морем, а також у вузькій приморській смузі, де проходить основний потік мігруючих тварин. Під час міграцій в Українському Приазов’ї кажани зупиняються для відпочинку в дуплах дерев у парках, штучних лісах і лісосмугах, різних урвищах та будівлях, які використовують як тимчасові сховки. У деяких із них кажани утворюють невеликі колонії і навіть зимують.
Видове різноманіття кажанів (CHIROPTERA) в українському Приазов’ї та особливості їхнього перебування за сезонами.
Keywords: Azov Region; detector; bat; wind power plant; research